ANALISIS YURIDIS DAN KELEMBAGAAN TERHADAP IMPLEMENTASI TILANG ELEKTRONIK: STUDI LITERATUR - Rigo, Seprigo; Reindy Rudagi; Septia Winar Diani; Septi Nurhazizah; Melva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology in the legal system has driven the modernization of law enforcement in Indonesia, including through the implementation of Electronic Traffic Law Enforcement (ETLE). This system relies on cameras and artificial intelligence to automatically detect traffic violations. However, its implementation still raises legal and institutional issues, particularly regarding the validity of electronic evidence, data privacy protection, and regional disparities in terms of supporting infrastructure and regulations. This study aims to analyze the implementation of the ETLE system in Indonesia from a normative and institutional legal perspective, as well as to evaluate its compliance with the principles of due process, privacy rights, and technology-based law enforcement governance. This study uses a normative legal approach with analysis of primary legal materials (laws and regulations), secondary scientific literature, and tertiary materials (legal dictionaries or encyclopedias). Data was collected through a literature review using purposive sampling techniques, then analyzed deductively and interpretatively against positive legal norms and principles of procedural justice. The results of the study show that although ETLE has the potential to improve efficiency and transparency, there are still discrepancies between its implementation practices and the positive legal framework, particularly regarding the status of electronic evidence and personal data protection. Institutional inconsistencies and disparities in implementation between regions also hinder its effectiveness. ETLE needs to be supported by reforms to criminal procedure regulations, strict data protection policies, and the establishment of an independent oversight body. Public awareness of digital law is key to creating a fair and sustainable technology-based law enforcement system.